Pembelajaran PBL Menggunakan Bahan Ajar Terintegrasi Nilai Spiritual untuk Meningkatkan Hasil Belajar dan Sikap Spiritual - Aisah Harahap; Ayi Darmana (Universitas Negeri Medan, 2020)
In the administration of education in Indonesia, it is usually only oriented towards the goal of making students into knowledgeable people, especially cognitive knowledge, while the spiritual value of students does not get the attention of educators. So that researchers are interested in conducting this research which aims to determine differences in student learning outcomes taught with integrated teaching materials of spiritual values and SMA/MA textbooks, differences in students' spiritual attitudes before and after being taught with teaching materials integrated spiritual values and the relationship between learning outcomes with attitudes spiritual students. Sampling using the Random Sampling technique. The instruments used were test and questionnaire instruments. Data analysis in the form of Independent Sample T-Test, Paired Sample T-Test and Correlation using IBM SPSS Statistics 22 for Windows. From the results of the study it can be concluded that there are differences in student learning outcomes taught by using integrated spiritual values teaching materials and SMA/MA textbooks, there are differences in students' spiritual attitudes before and after being taught with teaching materials integrated spiritual values and there is a relationship between learning outcomes and spiritual attitudes of students